1996
DOI: 10.1007/s002689900149
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal Pressure and Gastric Intramucosal pH: Is There an Association?

Abstract: This study evaluated the potential association between increased intraabdominal pressure (IAP) and abnormally low gastric intramucosal pH (pHi) (/= 20 mmHg and a pHi of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 23 publications
3
47
0
5
Order By: Relevance
“…Raeburn and coworkers [2], for example, reported an incidence of 36% of ACS in trauma patients after damage control laparotomy. A considerable number of reports have demonstrated that IAH exerts deleterious effects on the cardiovascular system and on pulmonary, renal, and gastrointestinal function [3,4,5,7]. Almost 30% of trauma patients requiring damage control laparotomy who show ACS develop multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…Raeburn and coworkers [2], for example, reported an incidence of 36% of ACS in trauma patients after damage control laparotomy. A considerable number of reports have demonstrated that IAH exerts deleterious effects on the cardiovascular system and on pulmonary, renal, and gastrointestinal function [3,4,5,7]. Almost 30% of trauma patients requiring damage control laparotomy who show ACS develop multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…When severe, tissue ischemia can result [32][33][34]. Clinically this can be monitored with gastric tonometry by recording the gastric mucosal pH, P CO 2 and GAP CO 2 :…”
Section: Gut Functionmentioning
confidence: 99%
“…In one study, 38% of patients admitted to an intensive care unit after major abdominal surgery had IAPs greater than 20 mm Hg. 19 The level of IAP at which the ACS occurs is variable. Clearly, variability in the physiologic response to a graded increase in pressure depends in part on the intravascular volume status of the patient as well as underlying pulmonary or renal dysfunction.…”
Section: Measurement Of Iapmentioning
confidence: 99%